Relationships between prostaglandin concentrations, a single nucleotide polymorphism in HSD17B12, and reproductive performance in dairy cows - J.L. Juengel; E.M.O. Mosaad; M.D. Mitchell; C.V.C. Phyn; M.C. French; E.D. Meenken; C.R. Burke; S. Meier (Journal of Dairy Science, 2022)
ABSTRACT: Prostaglandins are involved in multiple processes important for fertility, with previous work in mice highlighting a potential role for the HSD17B12 gene in prostaglandin biosynthesis. This study aimed to determine the associations among circulating prostaglandin concentrations, a missense SNP in the HSD17B12 gene predicted to disrupt protein function, and fertility traits in first-lactation Holstein-Friesian dairy cows. We used a study population of approximately 500 animals specifically bred to have either a positive (POS, +5%) or negative (NEG, −5%) genetic merit for fertility (FertBV). Genotypes of a previously identified SNP (rs109711583) in HSD17B12 were determined, with 116 animals genotyped as AA, 215 genotyped as AG, and 153 genotyped as GG. Plasma concentrations of prostaglandin E2 and the PGF2α metabolite PGFM were determined at 3 time points (12 mo of age, 4 d postpartum, and 5 wk postpartum during first lactation) in a selection of animals with AA and GG genotypes from both the POS and NEG FertBV groups (n = 33–40 in each genotype for each FertBV group). Binary reproductive traits (yes or no) examined included submission for artificial breeding in the first 3 or 6 wk of the seasonal breeding period; conception to first service; conception during the first 6 wk of the breeding period; and pregnant at the end of the breeding period. Uterine health at 6 wk after calving was examined by evaluating the percentage of polymorphonuclear leukocytes following uterine cytology and by scoring vaginal discharge based on the presence of purulent material. The 3-wk submission rate was increased in animals that carried the G allele of the missense SNP in HSD17B12, but no differences were present among genotypes for 6-wk submission rate. The trait was additive, with each increase of the G allele increasing the 3-wk submission rate by 6 to 7%. We did not observe any consistent associations between SNP alleles and circulating PGE2 concentrations; however, a complex 3-way interaction among time, fertility group, and SNP allele was present for PGFM concentrations. Plasma concentrations of PGE2 were increased approximately 40% at 5 wk postpartum in animals that were submitted for breeding within 3 or 6 wk of the start of the breeding season, and in those that conceived during the first 6 wk of breeding, compared with those that did not. Plasma concentrations of PGFM were decreased approximately 20% in those animals that conceived to their first service and tended to be decreased in animals that were pregnant at the end of the breeding period, compared with those that were not. In summary, associations were observed between the SNP in HSD17B12 and submission rate by d 21 of the breeding season, as well as between circulating prostaglandin concentrations and fertility traits, but the SNP was not consistently linked to changes in prostaglandin concentrations. Thus, the association between submission rate by d 21 of the breeding season and the SNP in HSD17B12 were unlikely driven by changes in prostaglandins.